RF and Microwave Afterglows in N2 Gas Mixtures for Surface Nitriding of TiO2 Films - Ricard, A.; Sarrette, J. P.; Oh, S. G.; Kim, Y. K. (Plasmas afterglows with \(N_2\) for Surface Treatments, 2021)
We report a detailed comparison between RF and microwave (HF) plasmas of N2 as well as N2-H2 and N2-CH4 in the corresponding afterglows by comparing densities of active species at nearly the same discharge conditions of tube diameter (5-6 mm), gas pressure (6-8 Torr), flow rate (0.6-1.0 slm) and applied power (50-150 W). The analysis reveals an interesting difference between the two cases; the length of the RF plasma (25 cm) is measured to be much longer than that of HF (6 cm). This ensures a much longer residence time (10-2s) of the active species in the N2 RF plasma [compared to that (10-3s) of HF], providing a condition for an efficient vibrational excitation of N2(X,v), making the RF plasma more vibrationally excited than the HF one. As a result of high VV plasma excitation in , RF, the densities of the vibrationally excited N2(X,v>13) molecules are higher in the RF afterglow than in the HF afterglow. Destruction of N2(X,v) on the quartz tube wall is estimated to be very similar between the two systems as can be inferred from the Yv destruction probability of N2(X,v>13) on the tube wall: (2-3)10-3 for both cases, obtained from a comparison between the density of N2(X,v>13) along the afterglows. Interestingly enough, densities of N-atoms and N2(A) metastable molecules in the afterglow regions, however, are measured to be very similar with each other. The measured lower density of N2+ ions than expected in the HF afterglow is rationalized from an high oxygen impurity in the HF setup since N2+ ions are very sensitive to oxygen impurity. In the N2-H2 studied gas mixtures, the N2(X,v>13) molecules were more destroyed in RF than in HF and inversely, the NH radicals and atoms are more populated. The TiO2 surface nitriding in RF was compared to HF at room gas temperature (RT). First, it was produced the most rich nitriding layers with a ratio N/Ti of 0.24 in the RF N2 late afterglow which was attributed to a low O-impurity in RF (a few ppm), compared to several 102 ppm in HF. Second, in the N2-H2 studied gas mixtures, the high H-atoms density appeared to be at the detriment of the nitriding layer with a N/Ti ratio reduced to a few percent in RF as for the HF case. In both RF and HF afterglows, the NH inclusion came with that of N.